Long-Term Outcomes of Anti-VEGF Therapy in Patients With Macular Edema Secondary to Retinal Vein Occlusion. (September 2017) - Young, Jason M.; Wai, Karen M.; Silva, Fabiana Q.; Conti, Felipe F.; Srivastava, Sunil K.; Ehlers, Justis P.; Rachitskaya, Aleksandra; Kaiser, Peter K.; Schachat, Andrew; Babiuch, Amy; Yuan, Alex; Singh, Rishi P.
Purpose: To evaluate long-term visual and anatomical outcomes of anti–vascular endothelial growth factor (VEGF) therapy for macular edema (ME) secondary to retinal vein occlusion (RVO) in routine clinical practice. Methods: Patients with ME secondary to hemi-RVO (HRVO), central RVO (CRVO), or branch RVO (BRVO) after initiating anti-VEGF therapy were followed for at least 36 months. Main outcomes were change in best visual acuity (BVA) and mean absolute change in central subfield thickness (CST) at 12, 24, 36, and 48 months. Results: Patients with BRVO showed significant increases in BVA that were maintained after 12, 24, 36, and 48 months (+11.03, +12.06, +10.71, and +9.26 letters, respectively; P < .05). CST significantly decreased after 12, 24, 36, and 48 months (−83.51, −67.93, −97.52, −127.85 µm, respectively; P < .05). In patients with CRVO/HRVO, significant improvements in BVA were seen at 12 and 24 months (+9.39 and +8.54 letters, respectively; P = .023). At 36 and 48 months, the visual gain was not significant (+2.64 and +3.42 letters, respectively; P > .05). For CST changes, there were significant decreases at 12, 24, and 36 months (−146.23, −149.54, and −166.44 µm, respectively; P < .05). At 48 months (−97.66 µm, P = .130), changes in CST were not significant. Conclusions: In routine clinical practice, visual and anatomical benefits of anti-VEGF agents in patients with BRVO were sustained at 36 and 48 months. For patients with CRVO/HRVO, anatomical improvements were maintained for 36, but not 48 months, while visual improvements were no longer maintained by 36 months.